Profit improvement analysis a case study of Air Kelantan Sdn Bhd - Mohd Nor, Ismail (2009)
Air Kelantan Sdn Bhd (AKSB) is the sole operator for treated water supply company in Kelantan. Total privatization was exercised in the year 1995. Being among the earliest company in Malaysia to be privatized in water industry, AKSB is supposed to progress and excel. Ironically, a company that is supposed to be a 'bench mark' in the water privatization concept has been lagged behind in terms of management and technology to later company such as Syarikat Air Johor Holding (SAJH), SYABAS, PUAS etc. The annual profit before tax was significantly reduced year after year. Year 2008 has been a dismal year for AKSB as the profit was diminished to 70 per cent compared to what AKSB has obtained in 2007. The income has soaring with the amount of almost RM 10 million from previous year but the profit before tax has shrank to a nasty figure. Therefore the biggest challenge for AKSB management now is to inflate the profit despite the rising operation costs. The analysis shows that AKSB suffers from its high operational costs, lost of income due to Non Revenue Water (NRW), low tariff and bad debts. This project studied the structure of AKSB and most importantly analyzing the NRW problem. AKSB is suffering the NRW at an average of 49 per cent which is among the highest rate in Malaysia. 1 per cent of NRW is equivalent to RM 1.80 million worth of money. In terms of Water Treatment Plant (WTP), the rising of operational costs is partly due to less efficiency of the plants where the production is reduced because of plants ageing. Some plants have to run on over capacity due to budget constraint on upgrading works. From the finding, AKSB has to resolve the NRW problem, as this issue will deteriorate the profitability further. Probably the restructuring process shall be exercised at management level in order to avoid the conflict among the top management and superintendents. The billing and collection units have to be efficient so that the bad debts and ageing collection can be improved. The productivity of employees is another crucial factor that determines the increment in profitability. Most of the employees in AKSB used to work with Jabatan Bekalan Air Kelantan. Working style as government servant is very much different with private employee. Even though AKSB has been privatized and exist more that 10 years ago, the attitude and working style has not been changed and the employees have difficulty to adapt to privatization. So in this case, AKSB has to shift the paradigm in order to remain competitive and able to generate significant profit.